The practicalities and pitfalls of establishing a policy‐relevant and cost‐effective soil biological monitoring scheme. (25th March 2013) - Faber, Jack H; Creamer, Rachel E; Mulder, Christian; Römbke, Jörg; Rutgers, Michiel; Sousa, J. Paulo; Stone, Dorothy; Griffiths, Bryan S
Abstract: A large number of biological indicators have been proposed over the years for assessing soil quality. Although many of those have been applied in monitoring schemes across Europe, no consensus exists on the extent to which these indicators might perform best and how monitoring schemes can be further optimized in terms of scientific and policy relevance. Over the past decade, developments in environmental monitoring and risk assessment converged toward the use of indicators and endpoints that are related to soil functioning and ecosystem services. In view of the proposed European Union (EU) Soil Framework Directive, there is an urgent need to identify and evaluate indicators for soil biodiversity and ecosystem services. The recently started integrated project, Ecological Function and Biodiversity Indicators in European Soils (EcoFINDERS), aims to address this specific issue within the EU Framework Program FP7. Here, we 1) discuss how to use the concept of ecosystem services in soil monitoring, 2) review former and ongoing monitoring schemes, and 3) present an analysis of metadata on biological indicators in some EU member states. Finally, we discuss our experiences in establishing a logical sieve approach to devise a monitoring scheme for a standardized and harmonized application at European scale. Integr Environ Assess Manag 2013; 9: 276–284. © 2013 SETAC